Corporate Ownership and Control in Victorian Britain - Graeme Acheson; Gareth Campbell; John D. Turner; Nadia Vanteeva (Queen's University Centre for Economic History (QUCEH), 2014)
Using ownership and control data for 890 firm-years, this paper examines the concentration of capital and voting rights in British companies in the second half of the nineteenth century. We find that both capital and voting rights were diffuse by modern-day standards. This implies that ownership was separated from control in the UK much earlier than previously thought, and given that it occurred in an era with weak shareholder protection law, it undermines the influential law and finance hypothesis. We also find that diffuse ownership is correlated with large boards, a London head office, non-linear voting rights, and shares traded on multiple markets.
Keywords: G32; K22; N24; 330; Corporate ownership and control; Law and finance hypothesis; British financial history; Shareholder protection law; corporate ownership and control